The role of entrepreneurial strategy, network ties, human and financial capital in new venture performance - Najib Ullah Khan; Shuangjie Li; Muhammad Nabeel Safdar; Zia Ullah Khan (Journal of Risk and Financial Management, 2019)
In the current era of globalization and competitive edge, the survival of newly established ventures has become a big challenge. Numerous studies have been carried out to discover factors that are essential for newly initiated ventures but the results are still fragmented. This study focuses on measuring the effect of entrepreneurial strategy, network ties, human capital and financial capital on new venture performance. A structured questionnaire was used to collect data from 196 registered firms located in the emerging market Pakistan. The results indicate that entrepreneurial strategy, network ties and financial capital have a significant positive effect, while human capital showed an insignificant effect on new venture performance. This research recommends owners and managers of new firms build effective entrepreneurial strategies, expand their networks with external bodies (other firms, government and financial institutions) to acquire useful resources that in turn can spur their performance. Further implications are discussed. Policy makers and responsible authorities are advised to encourage and support new ventures which in turn can contribute to GDP and economic development. Practical implications and suggestions are also discussed.
Keywords: 330; financial capital; network ties; human capital; entrepreneurial strategy; new venture performance; South Asia; Pakistan